The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Fifth ACM International Conference on Multimedia - MULTIMEDIA '97 1997
DOI: 10.1145/266180.266365
|View full text |Cite
|
Sign up to set email alerts
|

What should a wildebeest say? Interactive nature films for high school classrooms

Abstract: Nature documentaries play an important role in high school biology classrooms, yet they deliver a passive and biased account of the behavior of organisms. To engage students in more active problem solving around behavioral topics, we created an interactive video system called Animal Landlord. Part of a week-long curriculum designed to introduce concepts in behavioral ecology, Animal Landlord presents film clips of the Serengeti lion hunting its prey. Students select and annotate video frames with explanations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In particular, the data suggest that after completing the unit, students make fewer unwarranted inferences and are better at formulating coherent explanations ( Reiser et al, 2001 ;Sandoval, 1998 ). Similar results were found with the Animal Landlord software ( Smith & Reiser, 1997 ). A comparison of pre-and posttest essay questions also found that students ' essays on the posttest contained more causal arguments and a greater proportion of justifi ed points than students ' essays on the pretests ( Smith & Reiser, 1997 ).…”
Section: Scaffoldingsupporting
confidence: 72%
“…In particular, the data suggest that after completing the unit, students make fewer unwarranted inferences and are better at formulating coherent explanations ( Reiser et al, 2001 ;Sandoval, 1998 ). Similar results were found with the Animal Landlord software ( Smith & Reiser, 1997 ). A comparison of pre-and posttest essay questions also found that students ' essays on the posttest contained more causal arguments and a greater proportion of justifi ed points than students ' essays on the pretests ( Smith & Reiser, 1997 ).…”
Section: Scaffoldingsupporting
confidence: 72%
“…We have collected dam in the form of student and teacher interviews, work products, classroom video, and pm/post tests. We are still analyzing these data, and we have reported results from our final user trial concerning the prelpost tests elsewhere [19]. The open-ended essay questions used in the prelpost tests were drawn Corn university-level biology examinations and administered to students before and after the Animal Landlord intervention.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Finally, a scaffold similar to the Data Interpretation scaffold (BGuILE) could be used for asking students questions to guide their interpretation of the data (Smith and Reiser 1997). While this tool was not supported by empirical evidence (see Table 4), we believe it could be valuable for students.…”
Section: Investigation Phasementioning
confidence: 99%